Evaluation of marginal gap of Ni-Cr copings made with conventional and accelerated casting techniques - Pavan Kumar Tannamala; Nagarasampatti Sivaprakasam Azhagarasan; K Chitra Shankar (Wolters Kluwer Medknow Publications, 2013)
Context: Conventional casting techniques following the manufacturers' recommendations are time consuming. Accelerated casting techniques have been reported, but their accuracy with base metal alloys has not been adequately studied. Aim: We measured the vertical marginal gap of nickel-chromium copings made by conventional and accelerated casting techniques and determined the clinical acceptability of the cast copings in this study. Settings and Design: Experimental design, in vitro study, lab settings. Materials and Methods: Ten copings each were cast by conventional and accelerated casting techniques. All copings were identical, only their mold preparation schedules differed. Microscopic measurements were recorded at ×80 magnification on the perpendicular to the axial wall at four predetermined sites. The marginal gap values were evaluated by paired t test. Results: The mean marginal gap by conventional technique (34.02 μm) is approximately 10 μm lesser than that of accelerated casting technique (44.62 μm). As the P value is less than 0.0001, there is highly significant difference between the two techniques with regard to vertical marginal gap. Conclusion: The accelerated casting technique is time saving and the marginal gap measured was within the clinically acceptable limits and could be an alternative to time-consuming conventional techniques.